RIBA DAN BUNGA BANK DALAM PANDANGAN IBN QAYYIM DAN RELEVANSINYA DENGAN PERKEMBANGAN PERBANKAN ISLAM - Zahroh, Siti Khayisatuz (Institut Agama Islam Negeri Kendari, 2016)
Abstrack This research is based on library research which focus on discussing the problem that has existed since classical times, this discussion is a discussion of the concept of usury and bank interest in the view of IbnQayyim al-Jawziyya. Contemporary cleric is a cleric who often argue controversial, especially in discourses in the form of a controversial study. In this issue of this paper deals theview of IbnQayyim about riba at the time of the Prophet Muhammad until the time of IbnQayyim life. How interpretation riba second word in the Qur'an that until now remain in debateble between the ulama interpretation and jurisprudence specially by IbnQayyim own, third riba what if the opinion in view of IbnQayyim in relate with the view evolving Bank Interest in the modern world. The results of this study is that the definition of usury and interest in the view of IbnQayyim has differed fundamental. Secondly, that the bank interest now grown not purely as said riba during Nab Muhammad. Third IbnQayyim has the opinion that one and two were associated with a more contextual understanding of the interpretation in the life of the complex at this time. Keywords: Riba, Bank,and IbnQoyyim.